New narratives of disability : constructions, clashes, and controversies - Green, Sara E.; Loseke, Donileen R. (Emerald Publishing Limited, 2019)
This volume explores questions about narrative frameworks in disability research. Narrative is a omnipresent meaning-producing communication form in social life that is both cultural and personal. Public understandings of disability tend to follow a medical storyline in which disability is a personal tragedy to be treated through professional intervention - a frame that disempowers and fails to resonate with many disabled people. Scholars in disability studies and the social sciences have proposed an alternative that portrays social structures, forces, and attitudes as the problems to be resolved - a frame that, while empowering, may neglect, or even repress, some kinds of personal disability stories. This volume seeks to answer the call for richer, more diverse understandings of disability. We explore how narrative inquiry can broaden perspectives on disability to include pain, suffering, chronic illness, and episodic disability, as well as the perspectives of family members and caregivers, while also serving as a platform for dismantling prejudice and discrimination in order to promote positive social change.
Introduction: Exploring narrative as a social science framework on disability and disabled people / Donileen R. Loseke & Sara E. Green -- Part I: Cultural stories of disability and individual lives -- Chapter 1. Reframing the story of Helen Keller and Anne Sullivan: resisting (dis)ability stereotypes through an analysis of children's literature / Cheryl Najarian Souza -- Chapter 2. 'It's not that way you know, she has a good future': women's experiences of disability and community-based rehabilitation in Sri Lanka / Carmen Rebecca Britton & Laura Mauldin -- Chapter 3. Test anxiety: participation and exclusion beyond the institution / M. Nickie Coomer & Kenzie Latham-Mintus -- Chapter 4. Narratives of care and citizenship: managing "precariously normal" sons and daughters in an age of inequality / Linda M. Blum -- Chapter 5. 'More than a parent, you're a caregiver': narratives of fatherhood in families of adult sons and daughters with life-long disabilities / Heidi Steinour & Sara E. Green -- Part II: Cultural stories of disability and organizations -- Chapter 6.'You won't tell that you have schizophrenia, right? You should say you have a small depression': Organizational narratives of 'adjusted' workers with disabilities and the rhetoric of reassurance in France / Lisa D. Buchter -- Chapter 7. 'I want to go places on my own': a case-study of Virginia Commonwealth University ace-it in college / Stephanie J. Lau & Liza H. Weiss -- Chapter 8. More than therapy: conformity and resistance in an organizational narrative of disability and the performing arts / Melinda Leigh Maconi -- Part III: Cultural stories of disability and social policies -- Chapter 9. Narrative productions of problems and people in the Americans with Disabilities Amendment Act / Melissa Jane Welch -- Chapter 10. Institutional and personal narratives of chronic pain management: interrogating the medical and social models of disability / Loren E. Wilbers -- Chapter 11. Stuck in transition with you: variable pathways to in(ter)dependence for emerging adult men with mobility impairments / J. Dalton Stevens -- Chapter 12. Conflicting narratives of corporeal citizenship: Medicaid personal care attendant (pca) policy and experiences of cross-state move plans and pursuits / Brian R. Grossman -- Part IV: Cultural stories of disability and resistance -- Chapter 13. Neither victim nor super-hero: reflections on disability and mental health counseling / Richard A. Chapman -- Chapter 14. Self-study of intersectional and emotional narratives: narrative inquiry, disability studies in education, and praxis in social science research / Lisa Boskovich, Mercedes Adell Cannon, David Hernandez-Saca, Laurie Gutmann Kahn & Emily A. Nusbaum -- Chapter 15. Neoliberalism and the fight for the child: narratives of queer mothering / Ahoo Tabatabai -- Chapter 16. Sick and tired: narratives of contested illness in chronic fatigue syndrome blogs / Morgan V. Sanchez -- Chapter 17. 'We love each other into meaning': queer disabled Tumblr users constructing identity narratives through love and anger / Justine E. Egner -- Index.
Includes index.
Print version record.
Keywords: People with disabilities -- Social life and customs; People with disabilities -- Research; Social Science, People with Disabilities; Disability: social aspects